Depletion of Amyloid Precursor Protein (APP) Causes G0 Arrest in Non‐Small Cell Lung Cancer (NSCLC) Cells. Issue 6 (June 2015) - Sobol, Anna; Galluzzo, Paola; Weber, Megan J.; Alani, Sara; Bocchetta, Maurizio
<x xml:space="preserve">Abstract</x> We recently reported that Amyloid Precursor Protein (APP) regulates global protein synthesis in a variety of human dividing cells, including non‐small cell lung cancer (NSCLC) cells. More specifically, APP depletion causes an increase of both cap‐ and IRES‐dependent translation. Since growth and proliferation are tightly coupled processes, here, we asked what effects artificial downregulation of APP could have elicited in NSCLC cells proliferation. APP depletion caused a G0/G1 arrest through destabilization of the cyclin‐C protein and reduced pRb phosphorylation at residues Ser802/811. siRNA to cyclin‐C mirrored the cell cycle distribution observed when silencing APP. Cells arrested in G0/G1 (and with augmented global protein synthesis) increased their size and underwent a necrotic cell death due to cell membrane permeabilization. These phenotypes were reversed by overexpression of the APP C‐terminal domain, indicating a novel role for APP in regulating early cell cycle entry decisions. It is seems that APP moderates the rate of protein synthesis before the cell clears growth factors‐ and nutrients‐dependent checkpoint in mid G1. Our results raise questions on how such processes interact in the context of (at least) dividing NSCLC cells. The data presented here suggest that APP, although required for G0/G1 transitions, moderates the rate of protein synthesis before the cell fully commits to cell cycle progression following mechanisms, which seem additional to concurrent signals deriving from the PI3‐K/Akt/mTORC‐1 axis. APP appears to play a central role in regulating cell cycle entry with the rate of protein synthesis; and its loss‐of‐function causes cell size abnormalities and death. J. Cell. Physiol. 230: 1332–1341, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company